2022
DOI: 10.5812/semj.117171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Risk Factors of Development and Progression of Diabetic Retinopathy: A Review Study

Abstract: : Diabetes is a chronic, underlying, and common disease worldwide that imposes an enormous burden on the health system. Diabetic retinopathy (DR) is a serious complication in the eye caused by diabetes and may lead to visual impairment and blindness. The knowledge about the risk factors of DR is critical for the prevention of disease and developing treatment options. Moreover, DR is a multifactorial disease, and many studies have demonstrated various risk factors associated with it, such as hyperglycemia, hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Literature shows much evidence of association between increased HbA1c levels and DR incidence. The reason of lower HbA1c levels in NPDR and PDR groups could be better glycemic control which predicts better prognosis for DR 13 . A comparative study in Pakistani population reported significantly deranged serum lipid subfractions in DR group as compared to diabetics without DR but the former group showed significantly higher HbA1C than the diabetics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Literature shows much evidence of association between increased HbA1c levels and DR incidence. The reason of lower HbA1c levels in NPDR and PDR groups could be better glycemic control which predicts better prognosis for DR 13 . A comparative study in Pakistani population reported significantly deranged serum lipid subfractions in DR group as compared to diabetics without DR but the former group showed significantly higher HbA1C than the diabetics.…”
Section: Discussionmentioning
confidence: 98%
“…A comparative study in Pakistani population reported significantly deranged serum lipid subfractions in DR group as compared to diabetics without DR but the former group showed significantly higher HbA1C than the diabetics. 14 However, there is unclear evidence of differences in serum TG, cholesterol, and HDL levels between patients with DR and without DR. 13 There is evidence suggesting link between dyslipidemia in diabetes and insulin effects on liver apoprotein production, regulation of lipoprotein lipase, actions of cholesteryl ester transfer protein (CETP), and peripheral actions of insulin on adipose and muscle tissue. 15 In present study the decreased cholesterol and LDL levels in DR group than in the diabetes may be attributed to the better glycemic control and dyslipidemia management after diagnosis of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrates are other medications used to treat hyperlipidemia. A study showed that using the fenofibrate was associated with a lower rate of progression of DR (14). The National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) guidelines recommended a reasonable goal of LDL-cholesterol below 100 mg/dL (15).…”
Section: Introductionmentioning
confidence: 99%